Evaluation of Tubular Adhesively-Bonded Joints under Torsion - Oliveira , T. J. S.; Campilho , R. D. S. G.; Kirgiz , M. S.; Kumar , M. V.; Alzein , R. (Research and Developments in Engineering Research Vol. 6, 2023)
This work performs a numerical study in order to compare the torsional performance of three adhesives, in aluminium tubular joints (AW6082-T651), considering the variation of the main geometric parameters, such as overlap length (LO) and tubes’ thickness. The increasing demand for light weight, high quality and more cost effective product has led adhesive bonding to emerge as one of the primary ways of fastening structural members. Adhesive joints have been previously been designed empirically but now a day's data is available to design adhesive joints in an optimum way. In order to predict the strength, the Finite Element Method (FEM) was used with Cohesive Zone Models (CZM), whose analysis based itself on the internal stresses of the adhesive, namely the analysis of shear stress (txy) and joint strength, measured by the maximum torsional moment (Mm). To apply the torsion load, a reference point was created in the middle of the tube and it was connected to the cross-sectional face at one joint end, which allowed applying a torsional angle boundary condition and thus performing the tests. The joint meshes were built after defining the mesh sizes in each edge of the model. Previously, validation with experimental data was carried out. The technique was positively validated, and a significant geometry on Mm was found, except for LO.